Фестиваль "Сьомого травня" на узбережжі Чорного моря Туреччини - Оджал, О. (Народна творчість та етнографія, 2007)
May 7 in Giresun/Aksu has become an official festival in 1970 and now it is known and recognized internationally through efforts of both the natives and the local authorities. The rite coincides with the time when it is spring outside, and it gives joy to the rite. In Turkish shamanic mythology winter and spring symbolize death and life. In most cultures of the Northern hemisphere spring is considered to be the first day of the year. Therefore, the first day of the year is hope, salvation, blessing and joy. This festival is important because it means rebirth for both men and nature.